Rufaidah Al-Aslamiyah: Perawat Pertama di Dunia Islam (Abad 6-7 M.) - Saputra, Abdul Hamid; kusdiana, Ading; Rahmatillah, Tolib (Historia Madania: Jurnal Ilmu Sejarah, 2020)
The practice of Islamic health emerged in the sixth century AD influenced by three health traditions, namely ancient civilization, Bedouin Arabic, and Thibbun Nabawi. There is no much data related to health practice around the sixth century to the seventh century BC, except for nursing conducted by Rufaidah Al-Aslamiyah. She became an important figure in developing Islamic health practice and the involvement of women in the Islamic war. The purpose of this research is to determine the description of medicine/health in the Islamic world in the classical period and the role of Rufaidah Al-Aslamiyah in her involvement nursing field of the Islamic world. The method of this research is the historical research. The research method was carried out through four-stage, they are heuristics, criticism, interpretation, and historiography. Based on the research conducted, it could be stated that the practice of world health has emerged since 7,000 BC. In the sixth to seventh centuries Rufaidah Al-Aslamiyah had an important role in the development of world health practice. She started nursing for the first time in the Islamic world. Some of her important roles include: establishing a nursing school, participating in the war, establishing a field hospital, creating a nurse code of ethics, developing Islamic spiritual services, and being active in social activities in the city of Medina. It has also been proven that the first nursing knowledge was not conceived by Florence Nightingale in the 19th century, however, it has existed since the sixth century by Rufaidah Al-Aslamiyah. Â  Keywords: Health practice, Islamic health practice, nursing.